Peripheral Cystoid Degeneration Finding Using Intraoperative Optical Coherence Tomography in Rhegmatogenous Retinal Detachment - Nishitsuka K (Dove Medical Press, 2021)
Koichi Nishitsuka, Katsuhiro Nishi, Hiroyuki Namba, Yutaka Kaneko, Hidetoshi Yamashita Department of Ophthalmology and Visual Sciences, Yamagata University Faculty of Medicine, Yamagata, JapanCorrespondence: Koichi NishitsukaDepartment of Ophthalmology and Visual Sciences, Yamagata University Faculty of Medicine, Yamagata City, Yamagata, JapanTel +81 23-628-5374Fax +81 23-528-5377Email mlc12186@nifty.comPurpose: The interaction between the peripheral vitreous and retina is closely associated with the pathogenesis of rhegmatogenous retinal detachment (RRD). This study was conducted to examine the peripheral vitreous and retina in patients with RRD using intraoperative optical coherence tomography (iOCT).Methods: This retrospective study included 50 eyes of 50 patients (mean age 59.42 ± 10.80 years) that underwent vitrectomy using iOCT for treating RRD at the Yamagata University Hospital between September 2015 and September 2016. Each patient underwent 25-gauge pars plana vitrectomy that was performed by a single surgeon. During vitreous shaving with ocular indentation, the iOCT findings of the peripheral vitreous and retina were recorded and analyzed postoperatively.Results: In all patients, iOCT was able to detect the peripheral retina and vitreous around the vitreous base. Peripheral cystoid degeneration was detected on the peripheral retina of 27 eyes (54%). Furthermore, cystoid degeneration was detected around the retinal tear (5 patients), at the detached retinal area (8 patients), and at the attached retinal area (14 patients).Conclusion: iOCT enabled the evaluation of peripheral cystoid degeneration in patients with RRD. Cystoid degeneration might be associated with the pathogenesis of RRD.Keywords: peripheral retinal degeneration, rhegmatogenous retinal detachment, cystoid degeneration, intraoperative optical coherence tomography